Implementation of KH. Hasyim Asy’ari's Educational Concept in the Perspective of Jihad by Ibn Qayyim Al-Jawziyyah - Abdul Hakim; Didin Saepudin; Adian Husaini (PT FORMOSA CENDEKIA GLOBAL, 2024)
Education is a crucial factor in advancing a nation by enhancing its human resources. In Indonesia, the government prioritizes national education, including Islamic education, to nurture individuals who are intellectually capable, morally upright, and spiritually strong. The goal of national education, as outlined in Law No. 20 of 2003, is to develop students with integrity, independence, and a sense of democratic responsibility. Islamic education, especially through pesantren, plays a key role by emphasizing values such as character building, mutual cooperation, and a constructive understanding of jihad, focused on moral, social, and national progress. Historically, Indonesian scholars have used education to rally for independence, blending Islamic values with the principles of the nation. Today, pesantren and Islamic education adapt to modern challenges, fostering a balanced interpretation of Islamic values to contribute positively to society.